Self-adaptive Clustering Algorithm Based RBF Neural Network and its Application in the Fault Diagnosis of Power Systems - Jiang Huilan; Guan Ying; Li Dongwei; Xu Jianqiang (2005 IEEE/PES Transmission & Distribution Conference & Exposition: Asia and Pacific, 2005)
Radial basis function (RBF) neural networks (NNs) have been used in pattern recognition. The application of RBF network for fault diagnosis in high voltage transmission lines is presented in this paper. A self-adaptive clustering algorithm is proposed for the clustering process of RBFNN. The results of the simulation and fault tolerance test confirm that the proposed method can diagnose the fault of high voltage transmission lines quickly and correctly. Furthermore, it has the fault-tolerant ability that can identify the distorted input signals caused by the disturbance, and therefore it has the practical application value for real-timing information processing system